Pengaruh Corporate Social Responsibility (CSR) terhadap Persistensi Laba pada Perusahaan sektor Infrastruktur, Utilitas, dan Transportasi - Stephen Hadi Wibowo; Juniarti Juniarti (Business Accounting Review, 2016)
This study aimed to know the affect of Corporate Social Responsibility (CSR) to the persistence of earnings at companies in the infrastructure sector, utilities and transport. CSR activities have a positive impact on earnings persistence. Previous studies on the effect of CSR on the persistence of earnings were still very small and the results of previous studies also were inconsistent.This study used a sample from 2010 until 2014 on 76 companies in the infrastructure sector, utilities and transport. Processing and analysing of data in this study used SPSS version 22. The sample selection used purposive sampling method. This study also used firm size and leverage as variable controls. Results from this study could not show that CSR had an affect on earnings persistence. But firm size variable had an affect on earnings persistence